Géneros periodísticos en los medios de comunicación digital de Babahoyo - Espín Cabrera, Luis Sebastián (2020)
With the evolution and appearance of new technologies, the world has been more updated and involved in the world of communication, where the media have been part of these changes that leads to a transformation and displacement of them towards digital platforms, making their information almost immediately, leaving traditional mass media in the background. The human being has always been in the approach of innovations in the ways of communicating, where they have progressively been coupled and not only at the local level since digital media are present throughout the world, the majority of the population currently makes use of the internet which is the fundamental basis for the functioning of digital platforms, being there where communication professionals see the opportunity to implement new ways to disseminate information about news events. Virtual journalism is growing and advancing with greater force, where communicators have chosen to carry out journalistic work from digital platforms that in many cases arise as personal projects either due to lack of a job and thus generate income or belong to some medium traditional that also has a digital space.